Narrated video of a re‐do colposuspension. Issue 5 (1st September 2016) - Cardozo, Linda; Robinson, Dudley; Shakir, Fevzi
Abstract : Aims: To present a narrated video designed to demonstrate the steps involved in an open re‐do colposuspension. Methods: This was in a 70‐year‐old woman who presented with recurrent severe stress urinary incontinence. Urodynamics confirmed severe urodynamic stress incontinence, with no detrusor over activity. Her maximum urethral closure pressure (MUCP) was 8 cm/water. She previously had a total abdominal hysterectomy (TAH), bilateral salpingo‐oophorectomy (BSO) and colposuspension in 1998. Subsequently, she had a TVT in 2002 and then partial excision of the tape in 2003 due to erosion. This was followed by a Zuidex bulking agent in 2005 and subsequent TOT in 2006. After counselling she opted for a re‐do colposuspension. Results: If primary urinary incontinence surgery has failed the decision as to what treatment should then be undertaken is controversial. The options that are available include a repeat mid urethral sling (either retropubic or transobturator), urethral bulking agents, autologous fascial slings and re‐do colposuspension. Conclusion: A re‐do colposuspension is a sensible choice that is likely to achieve a better success rate than a second tape procedure. Although, colposuspension is an operation that most gynaecologists have now become deskilled in and rarely perform, mainly due to the popularity of tapes. This video demonstrates a re‐do colposuspension, with particular attention to the specific nuances that can results in a successful operation.